Optical imaging detection of microscopic mammary cancer in ErbB‐2 transgenic mice through the DA364 probe binding αvβ3 integrins. (24th April 2013) - Conti, Laura; Lanzardo, Stefania; Iezzi, Manuela; Montone, Monica; Bolli, Elisabetta; Brioschi, Chiara; Maiocchi, Alessandro; Forni, Guido; Cavallo, Federica
Abstract : Despite spontaneous tumor growth in genetically engineered mice being one of the most recognized tools for the in vivo evaluation of novel diagnostic and therapeutic anticancer compounds, monitoring early stage lesions in live animals is a goal that has yet to be achieved. A large number of targets for the molecular imaging of various diseases have been identified and many imaging technologies, including optical techniques are emerging. One of the most commonly exploited targets in tumor imaging is α v β 3 integrin, which plays an important role in the expansion, invasiveness and metastatic capability of a number of cancers, including breast cancer. The aim of this study was to set up an optical imaging method for the early detection of autochthonous mammary cancer in female BALB/c mice transgenic for the rat‐ErbB‐2 oncogene (BALB‐neuT). We show that DA364, a near‐infrared fluorescence arginine–glycine–aspartic acid cyclic probe, was taken up by neoplastic mammary glands and that its uptake increased with cancer progression. By contrast, the nonaccumulation of DA364 in the healthy mammary glands of virgin and lactating wild‐type mice suggests that the probe specifically targets breast cancers. Comparisons of optical imaging with whole‐mount and histological findings showed that DA364 allows the noninvasive visualization of atypical hyperplasia and microscopic foci of in situ carcinoma 2 months before mammary lesions become detectable by palpation. Moreover, DA364 was successfully used to monitor the outcome of anticancer vaccination. Therefore, it can be considered a promising early detection tool in near‐infrared noninvasive optical imaging for the early diagnosis of breast cancer. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : In this paper, we demonstrate that DA364, a near‐infrared fluorescence arginine–glycine–aspartic acid cyclic probe, is specifically taken up by neoplastic mammary glands of BALB/c mice transgenic for the rat ErbB‐2 oncogene. This uptake increases with cancer progression and allows the optical imaging noninvasive visualization of atypical hyperplasia and microscopic foci of in situ carcinoma 2 months before they become detectable by palpation. Moreover, DA364 can be successfully used to monitor the outcome of anticancer treatments, and can thus be proposed as a promising early detection tool in the imaging of mammary cancers.